2012
DOI: 10.4161/cib.21677
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically induced deformation and strain dynamics in actin stress fibers

Abstract: It is becoming evident that physical forces in the microenvironment play a key role in regulating many important aspects of cell biology. However, although mechanical cues are known to have clear effects over the long-term (days), the short-term (seconds to minutes) cellular responses to mechanical stimuli are less well characterized. In our recent study, we exposed committed fibroblast cells to well controlled nanoscale forces while simultaneously imaging force transduction through the actin cytoskeleton. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although the force application can be precisely measured at the AFM tip, it is virtually impossible to know what fraction of the force was transduced to underlying mitochondria because the cortical actin meshwork likely buffered a large fraction. Of note, forces in the nanonewton range are typically needed to induce deformation of the actin cytoskeleton ( Hadjiantoniou et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the force application can be precisely measured at the AFM tip, it is virtually impossible to know what fraction of the force was transduced to underlying mitochondria because the cortical actin meshwork likely buffered a large fraction. Of note, forces in the nanonewton range are typically needed to induce deformation of the actin cytoskeleton ( Hadjiantoniou et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Locating the AFM tip above the point of interest of the cell, e.g., the nucleus, allows the cell to be pressed with a well-defined nanonewton force, thus enabling observation of the mechanical response of the cytoskeleton. Such an approach enabled Hadjiantoniou et al to determine that the reaction to local force is not homogeneous in the whole cell [ 27 ]. It was confirmed that a highly localized deformation occurs far from the point of force application.…”
Section: Afm In Studies Of Physical Chemical and Mechanical Propmentioning
confidence: 99%
“…Micropipette aspiration Determination of bovine aortic endothelial cells adhesion [24] Optical tweezers Intercellular adhesion of the early embryo epithelial cells determined by cell displacement [25] Assessment of the influence of neighboring cells on the stiffness of breast cancer cells [26] Atomic force microscopy Detecting fibroblast cell inhomogeneities based on point cell pressing [27] Force mapping: Young's modulus maps e.g., of mammary gland cancer [28], primary human pulmonary artery endothelial cells [29][30][31], epithelial-like breast carcinoma cells [32] and elasticity maps e.g., of human aortic endothelial cells [33] Elasticity measurements of human umbilical vein endothelial cells, chondrocytes, fibroblasts, fibrosarcoma and hepatocellular carcinoma cells […”
Section: Mechanical Properties Measurementmentioning
confidence: 99%
“…Two types of fibers shape the cytoskeleton, namely, solid-like elastic fibers ( 45 ) and fluid-like viscous fibers ( 46 48 ). For a given mechanical load, a compliant cell will undergo more deformation than a stiff cell, and more fluid-like cells will dampen the force and will deform slower compared with highly elastic solid-like cells ( 49 ).…”
Section: Introductionmentioning
confidence: 99%